Geomorphology, lithofacies and sedimentary environment of lacustrine carbonates in the Eocene Dongying Depression, Bohai Bay Basin, China. (March 2020) - Liu, Shengqian; Jiang, Zaixing; He, Youbin; Dou, Luxing; Yang, Yang; Li, Yang; Han, Chao
Abstract: The Eocene lacustrine carbonates in the western Dongying Depression, Bohai Bay Basin were examined based on integrated analysis of 3D seismic data, cores, thin-sections, and geochemical testing. Seismic profiles and geomorphological mapping revealed a landmass-attached (semi-isolated) carbonate platform restricted by marginal syn-sedimentary faults and surrounded by three deep sags. 3D topographic analysis of the platform revealed six districts characterized by variable buried depths, topographic gradient, and fault combinations, including two flat-topped areas (PFW and SD; topographic gradient <4°) and four transitional zones above deep sags (P1, P2, S1, and S2; 4–10°). Eight lithofacies types were identified, forming five lithofacies associations: reef-shoal complex deposits, small bio-buildups, shoal-intershoal deposits, event flow deposits, and near-landmass mixed deposits. Well cross-sections revealed that facies distributions were closely associated with the geomorphological districts. Therefore, a geomorphology-dominated carbonate platform model was constructed, which highlighted the relationship of platform topography, hydrodynamic conditions, and facies distributions. The littoral facies is mainly composed of medium–high-energy deposits including reef-shoal and shoal sediments, which are mostly distributed in flat-topped areas. The sublittoral facies is dominated by low-to medium-energy deposits but influenced by storm activities, especially in the windward step-fault transitional zones. The profundal facies is positioned away from the platform marginal faults and joined with surrounding deep sags. Besides the regional geomorphology and its controlled hydrodynamic zones, the formation of such considerable lacustrine carbonates throughout the whole basin may have occurred because the global warming of late Eocene period induced sea transgression, which facilitated the development of lacustrine carbonates via marine-sourced reef-builders and biologically-induced carbonate precipitation. Furthermore, the East-Asian paleomonsoon climate influenced regional windfield may also have enhanced the prevailing southeast wind, which influenced the distribution of lithofacies and favorable reservoirs. Porosity-permeability analysis revealed that reservoir properties have a close relationship with geomorphology and lithofacies, thus geomorphology-associated facies prediction is essential for further hydrocarbon prospecting in this area. Highlights: A new geomorphology-dominated model was constructed to depict the detailed architecture of the lacustrine carbonate platform.. The global-warming-induced sea transgression faciliated the development of lacustrine carbonates in the Dongying Depression Geomorphological districts of the carbonate platform controlled the distributions of lithofacies and their associations.. Lacustrine carbonate reservoir properties were strongly controlled by geomorphology and lithofacies-caused heterogeneity. Paleomonsoon-climate-enhanced regional windfield could cause local redistribution of carbonate deposits on the platform.